Dental Caries Experience among the Children with Autism Spectrum Disorder in 3-15 Years - Malla, Manisha; Limbu, Senchhema; Dikshit, Parajeeta; Khanal, Sunita (Journal of Nepalese Association of Pediatric Dentistry, 2022)
Introduction: Dental caries remains the most prevalent, unmet health care need for children with special health care needs such as autism spectrum disorder. This study was carried out to help in providing a baseline data to enable comparison and future planning of dental services for autistic children.Objective: The study aims to evaluate the oral health status among the 3-15 years old children with Autism Spectrum Disorder in Kathmandu.Methods: A cross sectional study was done among 80 autistic children of age 3-15 years. Dental caries was measure by Decayed, Missing and Filled teeth. Data was entered and analyzed in SPSS.Results: The prevalence of the dental caries was found to be 66.3% (53) with mean dmft of 3.03 ± 3.71 and DMFT of 0.51 ± 1.78 among children with Autism Spectrum Disorder. Caries prevalence was higher in females compared to males. Among the carious teeth 94% were untreated.Conclusions: The prevalence of dental caries was high in children with Autism Spectrum Disorder with higher percentage of untreated decays, which emphasizes the need for immediate preventive as well as curative interventions.